Transformation of Islamic Education in the Era of Artificial Intelligence: An Ethical Review of the Use of Technology in the Curriculum - Farhan, Muhammad; Ali, Mohamad; Hafidz, Hafidz (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This research aims to analyze how AI affects the Islamic education curriculum and identify the ethical challenges that arise in the process. The approach used is Systematic Literature Review (SLR) based on the PRISMA guidelines by searching literature through the Scopus database using a combination of keywords "Islamic education", "Artificial Intelligence", "ethics", "technology", and "curriculum". Of the initial 49 articles, there were 8 articles that met the inclusion criteria analyzed thematically. The results of the study show that the integration of AI has driven the transformation of the Islamic education curriculum at three main levels: epistemological, pedagogical, and institutional. AI strengthens reflective and metacognitive learning models through adaptive learning systems and supports a digital-integrated curriculum that combines technology with Islamic values. However, significant ethical challenges also arise, such as data privacy issues, algorithmic bias, plagiarism, as well as the potential erosion of the authority of clerics and the value of spirituality in education. In addition, there is still a gap between the adoption of technology and the readiness of ethics and governance in accordance with the principles of maqāṣid al-sharī'ah. The practical implication is that Islamic educational institutions need to develop curriculum policies based on digital ethical literacy, AI capability building, and civilized data governance so that AI is not just a tool of efficiency, but a means of tazkiyat al-'aql wa al-nafs purification of reason and soul in modern Islamic education.